'We create our own small world': daily realities of mothers of disabled children in a South African urban settlement. Issue 1 (2nd January 2019) - van der Mark, Elise J.; Conradie, Ina; Dedding, Christine W. M.; Broerse, Jacqueline E. W.
Abstract: Parents of disabled children face many challenges. Understanding their experiences and acknowledging contextual influences is vital in developing intervention strategies that fit their daily realities. However, studies of parents from a resource-poor context are particularly scarce. This ethnographic study with 30 mothers from a South African township (15 semi-structured interviews and 24 participatory group sessions) unearths how mothers care on their own, in an isolated manner. The complexity of low living standards, being poorly supported by care structures and networks, believing in being the best carer, distrusting others due to a violent context, and resigning towards life shape and are shaped by this solitary care responsibility. For disability inclusive development to be successful, programmes should support mothers by sharing the care responsibility taking into account the isolated nature of mothers' lives and the impact of poverty. This can provide room for these mothers to increase the well-being of themselves and their children.